Peran Edukasi Kesehatan di Lingkungan Keluarga Dalam Pencegahan Penyakit Remaja - Suriatin Lubis (An Idea Health Journal, 2025)
The health of adolescents, both globally and in Indonesia, has become a serious concern due to the rising prevalence of conditions such as obesity, diabetes, and mental health disorders. Contributing factors include lifestyle habits and a lack of health knowledge. Health education within the family environment is considered essential for preventing diseases among adolescents. This study aims to examine the extent to which family health education (variable X) influences disease prevention among adolescents (variable Y). The study population consists of 1,000 parents in the city of Medan, with a sample size of 120 respondents. Simple linear regression analysis was used to assess the impact of family health education on adolescent disease prevention. The findings indicate that family health education has a significant and positive influence on preventing diseases in adolescents, with a T-value of 2.508 and a significance level of 0.019 (p < 0.05). The better the health education within the family environment, the more effective disease prevention efforts are among adolescents. In conclusion, families play a vital role in supporting adolescent health through health education.